SIRT1 Regulates N6‐Methyladenosine RNA Modification in Hepatocarcinogenesis by Inducing RANBP2‐Dependent FTO SUMOylation. Issue 6 (22nd October 2020) - Liu, Xiaoming; Liu, Jianye; Xiao, Wen; Zeng, Qinghai; Bo, Hao; Zhu, Yuxing; Gong, Lian; He, Dong; Xing, Xiaowei; Li, Ruhong; Zhou, Ming; Xiong, Wei; et al.
Abstract : Background and Aims: Hepatocellular carcinoma (HCC) is associated with high malignancy rates. Recently, a known deacetylase silent information regulator 1 (SIRT1) was discovered in HCC, and its presence is positively correlated with malignancy and metastasis. N 6 ‐methyladenosine (m 6 A) is the most prominent modification, but the exact mechanisms on how SIRT1 regulates m 6 A modification to induce hepatocarcinogenesis remain unclear. Approach and Results: Here we demonstrate that SIRT1 exerts an oncogenic role by down‐regulating fat mass and obesity‐associated protein (FTO), which is an m 6 A demethylase. A crucial component of small ubiquitin‐related modifiers (SUMOs) E3 ligase, RANBP2, is activated by SIRT1, and it is indispensable for FTO SUMOylation at Lysine (K)‐216 site that promotes FTO degradation. Moreover, Guanine nucleotide‐binding protein G (o) subunit alpha (GNAO1) is identified as m 6 A downstream targets of FTO and tumor suppressor in HCC, and depletion of FTO by SIRT1 improves m 6 A + GNAO1 and down‐regulates its mRNA expression. Conclusions: We demonstrate an important mechanism whereby SIRT1 destabilizes FTO, steering the m 6 A + of downstream molecules and subsequent mRNA expression in HCC tumorigenesis. Our findings uncover a target of SIRT1 for therapeutic agents to treat HCC.